Entrevue guidée avec Jacques Leplat - Esther Cloutier; Corinne Gaudart (Perspectives Interdisciplinaires sur le Travail et la Santé)
Now 84 years of age, Jacques Leplat, a psychologist from the École Pratique des Hautes Études in Paris, has been working for more than 50 years on formalizing the concepts of the « analysis of work in ergonomic psychology ». He has also contributed to the advancement of knowledge in the fields of training and safety. PISTES met with him so that we could let our readers know about him and to discuss with him his current concerns.